Cronobacter sakazakii ATCC 29544 Autoaggregation Requires FliC Flagellation, Not Motility - Hoeflinger, Jennifer L.; Miller, Michael J. (Frontiers in Microbiology, 2017)
Cronobacter sakazakii is an opportunistic nosocomial and foodborne pathogen that causes severe infections with high morbidity and mortality rates in neonates, the elderly, and immunocompromised individuals. Little is known about the pathogenesis mechanism of this pathogen and if there are any consequences of C. sakazakii colonization in healthy individuals. In this study, we characterized the mechanisms of autoaggregation in C. sakazakii ATCC 29544 (CS29544). Autoaggregation in CS29544 occurred rapidly, within 30 min, and proceeded to a maximum of 70%. Frameshift mutations in two flagellum proteins (FlhA and FliG) were identified in two nonautoaggregating CS29544 clonal variant isolates. Strategic gene knockouts were generated to determine if structurally intact and functional flagella were required for autoaggregation in CS29544. All structural knockouts (ΔflhA, ΔfliG, and ΔfliC) abolished autoaggregation, whereas the functional knockout (ΔmotAB) did not prevent autoaggregation. Complementation with FliC (ΔfliC/cfliC) restored autoaggregation. Autoaggregation was also disrupted by the addition of exogenous wild-type CS29544 filaments in a dose-dependent manner. Finally, filament supercoils tethering neighboring wild-type CS29544 cells together were observed by transmission electron microscopy. In silico analyses suggest that direct interactions of neighboring CS29544 FliC filaments proceed by hydrophobic bonding between the externally exposed hypervariable regions of the CS29544 FliC flagellin protein. Further research is needed to confirm if flagella-mediated autoaggregation plays a prominent role in C. sakazakii pathogenesis.